Current situation and future directions of lung cancer risk factor awareness in Palestine: a cross-sectional study. Issue 1 (17th January 2023) - Elshami, Mohamedraed; Mansour, Ahmad; Alser, Mohammed; Al-Slaibi, Ibrahim; Abukmail, Hanan; Shurrab, Hanan; Qassem, Shahd; Usrof, Faten Darwish; Alruzayqat, Malik; Aqel, Wafa; Nairoukh, Roba; Kittaneh, Rahaf; et al.
Abstract : Objectives: To evaluate lung cancer (LC) risk factor awareness among Palestinians and identify factors associated with good awareness. Design: Cross-sectional study. Settings: Participants were recruited using convenience sampling from hospitals, primary healthcare centres (PHCs) and public spaces located at 11 governorates in Palestine. Participants: Of 5174 approached, 4817 participants completed the questionnaire (response rate=93.1%). A total of 4762 questionnaires were included: 2742 from the West Bank and Jerusalem (WBJ) and 2020 from the Gaza Strip. Exclusion criteria were working or studying in a health-related field, having a nationality other than Palestinian and visiting oncology departments or clinics at the time of data collection. Tool: A modified version of the validated LC Awareness Measure was used for data collection. Primary and secondary outcomes: The primary outcome was LC risk factor awareness level as determined by the number of factors recognised: poor (0–3), fair (4–7) and good (8–10). Secondary outcomes include the recognition of each LC risk factor. Results: Smoking-related risk factors were more often recognised than other LC risk factors. The most recognised risk factors were 'smoking cigarettes' (n=4466, 93.8%) and 'smoking shisha (waterpipes)' (n=4337, 91.1%). The least recognised risk factors were 'having a close relative with LC' (n=2084, 43.8%) and 'having had treatment for any cancer in the past' (n=2368, 49.7%). A total of 2381 participants (50.0%) displayed good awareness of LC risk factors. Participants from the WBJ and the Gaza Strip had similar likelihood to display good awareness (50.6% vs 49.1%). Being≥45 years, having higher education and monthly income, knowing someone with cancer and visiting hospitals and PHCs seemed to have a positive impact on displaying good awareness. Conclusion: Half of study participants displayed good awareness of LC risk factors. Educational interventions are warranted to further improve public awareness of LC risk factors, especially those unrelated to smoking.